Associative polyurethane modifiers of rheological properties of aqueous dispersions of polymers. Part 2, The effects of selected factors on modifiers’ activities - Przybylski, J. (Polimery, 2022)
An article is a continuation of literature review concerning the titled polyurethane (PUR) modifiers. The effects of modifiers’ structures the lengths of hydrophobic and hydrophilic segments of PUR chain, molecular weight distributions of hydrophilic segments and the features of substrates used in PUR syntheses [type of diisocyanate, substitution degree of hydroxyl groups in poly(ethylene oxide) (PEG)] on the efficiency of modification of rheological properties of aqueous polymeric dispersions (Fig. 1) were discussed. Dependence of this efficiency on the factors not related to modifiers’ structures, namely additional presence of organic solvent in the system (Fig. 2), surfactant or PUR modifier content was also characterized.